Organizational Leadership Development in Malaysia: Current Practices, Challenges and Future Potentials - Victoria, Jonathan; Hana, Hamidi (Palgrave Macmillan US, 2017)
As an emerging economy, Malaysia depends not only on foreign investment, good infrastructure and technology but also on the talent and leadership abilities of its future leaders. In the Malaysian context, the importance of leadership is reflected in the government’s support for human capital development and developing capable leaders through investment in leadership development initiatives. This chapter presents some of the leadership development practices, challenges and potentials in the public and private sectors in Malaysia. It includes an overview of research on organizational leadership in Malaysia; a description of current leadership development practices, programs and systems in the public and private sectors, including a description of a national leadership development initiative; a look at some challenges to leadership development; and implications for research and practice for sustainable leadership development in the country.